Caribbean Report 03-03-1992 - Ransome, Debbie (anchor); Pierre, Eric (interviewee); Ingram, Simon (correspondent); Webster, Rudi (interviewee); Stainer, Robin (interviewee); Ras, Blue (interviewee); Ras, Kassa (interviewee) (The British Broadcasting Corporation, 1992)
Trade unionists in London have pledged support with Grenada’s trade union movement to shut down the country over stalled wage negotiations with government and the private sector. An investigation is being called into claims that Senior EC Commissioner Abel Matutes has business interest in Hotel Dominicana Fiesta which was the venue for a major ACP-EC meeting. The pressure mounting from the World Cup cricket match between West Indies and South Africa is being viewed as a psychological clash with the focus on the skills of Captain Richie Richardson. Trinidad and Tobago, Grenada and Jamaica answer the call by London based commodities analyst Robin Stainer for Caribbean cocoa growers to upgrade the quality of cocoa to make its mark on an already slumping market. Finally, Ras Blue of the Centenary Committee for Rastafari and Ras Kassa of the London branch of the Ethiopian World Federation plan events in celebration of the birth of Emperor Haile Selassie I of Ethiopia.
1. Headlines (00:00-00:36)
2. Grenada’s trade union movement plans to shut down the country over stalled wage negotiations. Eric Pierre, Vice President of Grenada’s trade union council discusses planned action (00:37-03:47)
3. EC Commissioner Abel Matutes faces allegations of using his influence to host a major ACP-EC meeting at a hotel in Santo Domingo in which he might have shares. Correspondent Simon Ingram reports from Brussels (03:48-06:04)
4. The West Indies cricket team plays South Africa in their first international match after 22 years. Correspondent Hugh Crosskill speaks with sports psychologist Dr. Rudy Webster (06:05-09:13)
Keywords: Wages -- Grenada; Collective bargaining -- Grenada; Matutes, Abel; Conflict of interests -- Belgium -- Brussels; Cricket -- Tournaments -- West Indies; Cricket -- Tournaments -- South Africa; Cocoa trade -- Trinidad and Tobago; Cocoa trade -- Grenada; Cocoa trade -- Jamaica; Cocoa trade -- Research -- Caribbean Area; Cocoa trade -- Quality -- Caribbean Area; Haile Selassie I, Emperor of Ethiopia, 1892-1975; Rastafarians -- Centennial celebrations, etc.; Rastafarians -- England -- London; Ras Blue -- Centenary Committee for Rastafari; Ras Kassa, (Gerald Maxwell Haynes) -- Ethiopian World Federation (London); World Cup (Cricket) (1992 : Australia; New Zealand)